Quiescent bilayers at the mica-water interface - Speranza, F; Pilkington, G; Dane, T; Cresswell, P; Li, P; Jacobs, R; Arnold, T; Bouchenoire, L; Thomas, R; Briscoe, W (2013)
Despite extensive studies with many experimental techniques, the morphology and structure of the self-assembled aggregates of quaternary alkyl ammonium bromides (CnTABs; where n denotes the number of hydrocarbons in the surfactant tail) at the solid-liquid interface remains controversial, with results from atomic force microscopy (AFM) imaging pointing to a variety of surface aggregates such as cylinders and surface micelles, whilst surface force measurements and neutron reflectivity (NR) measurements reporting bilayer structures. Using a home-built liquid cell that employs the "bending mica" method, we have performed unprecedented synchrotron X-ray reflectometry (XRR) measurements to study the adsorption behaviour of a C nTAB series (n = 10, 12, 14, 16 and 18) at the mica-water interface at different surfactant concentrations. We find that our XRR data cannot be described by surface aggregates such as cylindrical and spherical structures reported by AFM studies. In addition we have observed that the bilayer thickness, surface coverage and the tilt angle all depend on the surfactant concentration and surfactant hydrocarbon chain length n, and that the bilayer thickness reaches a maximum value at approximately the critical micellisation concentration (∼1 cmc) for all the CnTABs investigated. We propose that CnTABs form disordered bilayer structures on mica at concentrations below cmc, whilst at ∼1 cmc they form more densely packed bilayers with the tails possibly tilted at an angle θt ranging from ∼40 to 60° with respect to the surface normal in order to satisfy the packing constraints due to the mica lattice charge, i.e. so that the cross-section area of the tilted chain would match that of the area of the lattice charge (As ≅ 46.8 Å2). As the surfactant concentration further increases, we find that the bilayer thickness decreases, and we ascribe this to the desorption of surfactant molecules, which recovers certain disorder and fluidity in the chain and thus leads to interdigitated bilayers again. In light of our XRR results, previously unattainable at the mica-water interface, we suggest that the surface aggregates observed by AFM could be induced by the interaction between the scanning probe and the surfactant layer, thus representing transient surface aggregation morphologies; whereas the CnTAB bilayers we observe with XRR are intrinsic structures under quiescent conditions. The suggestion of such quiescent bilayers will have fundamental implications to processes such as lubrication, self-assembly under confinement, detergency and wetting, where the morphology and structure of surfactant layers at the solid-liquid interface is an important consideration. © 2013 The Royal Society of Chemistry.